Oncology patients' and oncology nurses' views on palliative chemotherapy: A cross-sectional comparison. Issue 5 (October 2021) - Shepherd, Jan; Waller, Amy; Sanson-Fisher, Rob; Zdenkowski, Nicholas; Douglas, Charles; Clark, Katherine
ABSTRACT: Background: Palliative chemotherapy may be offered to patients with incurable cancer with the goal of extending life and improving quality of life. However, the adverse effects that may be associated with chemotherapy can negatively impact patients' quality of life. Oncology nurses have an integral role in caring for patients during the decision-making process and may understand the potential implications of treatment options being offered to patients. Objectives: (1) To compare the views of medical oncology outpatients and oncology nurses about palliative chemotherapy near the end of life. (2) To examine the reasons oncology nurses gave for choosing not to receive palliative chemotherapy. Design: Cross-sectional comparison study. Settings and participants: A total of 194 patients, aged 18 years or over with a confirmed diagnosis of cancer who were attending a medical oncology outpatient clinic for their second or subsequent appointment completed a pen and paper survey between September 2015 and January 2016. One hundred and seven nurses who were members of an oncology nursing society or employed in an oncology setting in a participating metropolitan hospital completed an online survey between May 2018 and July 2019. Outcome measures: Participants were presented with data derived from the Coping with Cancer study comparing six quality of life and care outcomes for patients who received, or did not receive, palliative chemotherapy in the last 6 months of life. Participants were asked to consider the data and indicate what option they would choose if they were in the same situation. Choices included: have chemotherapy; do not have chemotherapy; and unsure. Participating nurses were also asked to provide reasons for their choices. Results: Three-quarters of participating nurses indicted they would not have palliative chemotherapy if it was offered to them, compared to just over one-third of people with cancer (p < 0.001). The top three reasons participating nurses gave for not having palliative chemotherapy were: wanting to make the most of their remaining time; increasing the chance of dying in the location of their choice; and the limited benefit of palliative chemotherapy in the last 6 months of life. Conclusion: Nurses in this study were significantly less likely than patients to indicate a willingness to have palliative chemotherapy if they were in the last 6 months of life. Further research is needed to examine how nurses' knowledge and experience can help patients to make informed decisions about their care with the goal of achieving an end-of-life experience that best aligns with their wishes.